Exploring Transformational Leadership Behavior in Higher Education: A Case Study from Sudan - Onia, Saifaldin Idris; Dafaallah, Adil Mohammed (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2025)
Transformational leadership is comprised of four dimensions named idealized influence, intellectual stimulation, inspirational motivation, and individualized consideration. To this end, the purpose of this study was to explore transformational leadership behavior in higher education with focus on Al-Gezira University. Therefore, this study followed survey research design. 332 participants were taken through stratified random sampling techniques. Data was collected from teachers using closed ended questionnaire. To analyze data, mean scores, and one sample t-test was used. The study found that idealized influence, inspirational motivation, intellectual stimulation, and individual consideration were practiced at Gezira University. The findings confirmed that Gezira University demonstrated transformational leadership behavior. The study recommended a Gezira University should organize training program, courses and workshops to equip staff members with leadership skills and competencies that enhance the practices of transformational leadership.